Prospective Use of Brown Spider Venom Toxins as Therapeutic and Biotechnological Inputs - Gremski, Luiza Helena; Matsubara, Fernando Hitomi; Polli, Nayanne Louise Costacurta; Antunes, Bruno Cesar; Schluga, Pedro Henrique de Caires; Justa, Hanna Câmara da; Minozzo, João Carlos; Wille, Ana Carolina Martins; Senff-Ribeiro, Andrea; Veiga, Silvio Sanches (Frontiers in Molecular Biosciences, 2021)
Brown spider (genus Loxosceles) venoms are mainly composed of protein toxins used for predation and defense. Bites of these spiders most commonly produce a local dermonecrotic lesion with gravitational spread, edema and hemorrhage, which together are defined as cutaneous loxoscelism. Systemic loxoscelism, such as hematological abnormalities and renal injury, are less frequent but more lethal. Some Loxosceles venom toxins have already been isolated and extensively studied, such as phospholipases D (PLDs), which have been recombinantly expressed and were proven to reproduce toxic activities associated to the whole venom. PLDs have a notable potential to be engineered and converted in non-toxic antigens to produce a new generation of antivenoms or vaccines. PLDs also can serve as tools to discover inhibitors to be used as therapeutic agents. Other Loxosceles toxins have been identified and functionally characterized, such as hyaluronidases, allergen factor, serpin, TCTP and knottins (ICK peptides). All these toxins were produced as recombinant molecules and are biologically active molecules that can be used as tools for the potential development of chemical candidates to tackle many medical and biological threats, acting, for instance, as antitumoral, insecticides, analgesic, antigens for allergy tests and biochemical reagents for cell studies. In addition, these recombinant toxins may be useful to develop a rational therapy for loxoscelism. This review summarizes the main candidates for the development of drugs and biotechnological inputs that have been described in Brown spider venoms.